2017
DOI: 10.1186/s12936-017-1687-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plasmodium vivax metacaspase 1 and Plasmodium vivax multi-drug resistance 1 genes of field isolates from Mauritania, Sudan and Oman

Abstract: Background Plasmodium vivax is the second most important human malaria parasite, widely spread across the world. This parasite is associated with important issues in the process toward malaria elimination, including potential for relapse and increased resistance to chloroquine. Plasmodium vivax multi-drug resistant (pvmdr1) is suspected to be a marker of resistance although definitive evidence is lacking. Progress has been made in knowledge of biological factors affecting parasite growth, including mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Mosquito feeding experiments employing either direct skin or membrane feeding fail to represent numerous participant-, mosquito-, and parasite-related factors that are critical to transmission. These critical factors include variance among mosquito vectors in biting preferences 28 , behaviors 26 , and success 29 ; among parasites in replication rates 27 and gametocyte production 30 ; and among participants in exposure to vectors 31 and care-seeking behavior 32 . Similarly, this complexity also confounds the use of gametocyte prevalence or density as a proxy for transmission 33 , which may more precisely define which infections can rather than do transmit.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito feeding experiments employing either direct skin or membrane feeding fail to represent numerous participant-, mosquito-, and parasite-related factors that are critical to transmission. These critical factors include variance among mosquito vectors in biting preferences 28 , behaviors 26 , and success 29 ; among parasites in replication rates 27 and gametocyte production 30 ; and among participants in exposure to vectors 31 and care-seeking behavior 32 . Similarly, this complexity also confounds the use of gametocyte prevalence or density as a proxy for transmission 33 , which may more precisely define which infections can rather than do transmit.…”
Section: Discussionmentioning
confidence: 99%
“…Dry blood films from 45 different patients were obtained by scrapping off the surface of the smear with a scalpel and re-suspending in 100 μL of phosphate-buffered saline (PBS) [ 33 ]. Genomic DNA was extracted using a QIAamp DNA mini kit (Qiagen) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the genetic diversity of Pv MCA1, eighty-three wild isolates of P. vivax from Juruá Valley in the Brazilian Amazon were submitted to DNA sequencing for gene segment coding the consensus His372-Cys428 catalytic dyad (13). In contrast to work by Sow et al, 15 in which the majority of isolates (24/28, 85.7%) presented amino acid substitution in both catalytic dyad and an upstream cysteine residue (Cys305) also inserted in the peptidase C14 domain, all the isolates herein studied showed complete nucleotide sequence identity each other as well as compared to P. vivax Sal-1 reference, with conservation of all the amino acid residues successfully sequenced (A288 to K446) ( Fig. 1 ), supporting that the proteolytic activity of Pv MCA1 may be critical to the parasite.…”
mentioning
confidence: 67%
“…They present structural similarity to metazoan caspases, both having a conserved His-Cys catalytic dyad in the large (p20) domain, but different substrate specificity. 13 In Plasmodium genomes, three metacaspases (MCA1-3) occur 14 and a study performed with field isolates from Mauritania, Sudan and Oman showed that P. vivax metacaspase 1 ( Pv MCA1) can present single nucleotide polymorphisms in the putative His-Cys catalytic residues, 15 which in some extent can be a factor limiting the eligibility of Pv MCA1 as a novel drug target for vivax malaria. In the present study, therefore, we investigated the genetic diversity of the Pv MCA1 catalytic domain in a P. vivax population from the main malaria hotspot in Brazil - a country where this plasmodial species is highly prevalent (~90%).…”
mentioning
confidence: 99%
See 1 more Smart Citation